Assessment of mechanical properties by nano- and microindentation of alumina/zirconia composites. (2021) - Sadowski, Tomasz; Łosiewicz, Kamil; Boniecki, Marek; Szutkowska, Magdalena
Abstract: CCs (Ceramic Composites) are used as structural materials due to their exceptional combination of mechanical properties [56] . Therefore, the paper presents research results for common 3 mol% Y2 O3 stabilised ZrO2 and pure Al2 O3 ceramics as well as four Al2 O3 /ZrO2 composites. The above mentioned samples are different in composition ratio of: 20, 40, 60 and 80 wt% of Al2 O3 content. All of the samples were polished on one side. The tests were carried out at the Nanoindentation Tester (NHT 3 ), Microindentation Tester (MHT 3 ) and Hardness Tester. Four load levels were used: 0.002 N, 0.2 N, 20 N and 98.1 N. Berkovich tip was used for the smallest load and Vickers diamond tip for the other. The analysis of the results was carried out in the Indentation software, obtaining the force – depth indentation curves, plane strain modulus E* and Vickers hardness HV . This type of data is also necessary to properly build a numerical model.